Transforming growth factor β‐inhibitor Repsox downregulates collagen expression of scleroderma dermal fibroblasts and prevents bleomycin‐induced mice skin fibrosis. Issue 11 (25th August 2017) - Ide, Maho; Jinnin, Masatoshi; Tomizawa, Yukiko; Wang, Zhongzhi; Kajihara, Ikko; Fukushima, Satoshi; Hashizume, Yoshinobu; Asano, Yoshihide; Ihn, Hironobu
Abstract: Inhibition of transforming growth factor (TGF)‐β1 signalling may be one of the most reliable approaches to treat skin fibrosis of scleroderma. Although there have been many basic researches of TGF‐β blockade reagents, few of them were proved to have inhibitory effects on fibrosis both in vitro and in vivo. In this study, we randomly chose four commercially available low molecular weight compounds (Repsox, LY2109761, LY364947 and K02288) from TGF‐β1 inhibitor library, and compared their antifibrotic effects in vitro and in vivo. We demonstrated that Repsox has the most potent inhibitory effects on TGF‐β‐induced expression of CTGF and collagen of cultured normal dermal fibroblasts in vitro and their constitutive overexpression of scleroderma fibroblast in vitro. In addition, Repsox could attenuate skin fibrosis by bleomycin in vivo, via the downregulation of CTGF or collagen. Our results may facilitate clinical trial of Repsox against fibrotic diseases in future.